Flux melting of metal–organic frameworks. Issue 12 (20th February 2019) - Longley, Louis; Collins, Sean M.; Li, Shichun; Smales, Glen J.; Erucar, Ilknur; Qiao, Ang; Hou, Jingwei; Doherty,, Cara M.; Thornton, Aaron W.; Hill, Anita J.; Yu, Xiao; Terrill, Nicholas J.; et al.
Abstract : We show flux melting by using a liquid MOF as a solvent for a secondary, non-melting MOF component. Abstract : Recent demonstrations of melting in the metal–organic framework (MOF) family have created interest in the interfacial domain between inorganic glasses and amorphous organic polymers. The chemical and physical behaviour of porous hybrid liquids and glasses is of particular interest, though opportunities are limited by the inaccessible melting temperatures of many MOFs. Here, we show that the processing technique of flux melting, 'borrowed' from the inorganic domain, may be applied in order to melt ZIF-8, a material which does not possess an accessible liquid state in the pure form. Effectively, we employ the high-temperature liquid state of one MOF as a solvent for a secondary, non-melting MOF component. Differential scanning calorimetry, small- and wide-angle X-ray scattering, electron microscopy and X-ray total scattering techniques are used to show the flux melting of the crystalline component within the liquid. Gas adsorption and positron annihilation lifetime spectroscopy measurements show that this results in enhanced, accessible porosity to a range of guest molecules in the resultant flux melted MOF glass.